Ethical Issues in Counseling with Gay and Lesbian Clients: Conversion Therapy and Confidentiality Limits - Tam, Ekman P. C. (The Journal of pastoral care, 1997)
Examines the contemporary dispute over conversion therapy with gay and lesbian clients and explores the dilemma of confidentiality limits with clients who have HIV. Suggests frameworks for pastoral counselors to consider in making decisions regarding this population of clients.